Ipsa senectus morbus est? Approaching the unmet needs in geriatric depression: results from a national survey of medical experts - Albert, Umberto; Tomasetti, Carmine; Antonelli Incalzi, Raffaele; Cicolin, Alessandro; Padovani, Alessandro; Zanetti, Michela; Maina, Giuseppe (Frontiers in Psychiatry, 2025)
IntroductionOne of the main challenges of “real-world” management of depression is represented by geriatric depression, which is common and under-diagnosed. Depressive disorders represent the leading contributors to mental health-related global burden, and they are often diagnosed in the context of many comorbid disorders, such as cardiovascular disorders, Stroke, Parkinson’s Disease, Major Neurocognitive Disorders and Headache, thus worsening their outcomes. Depression, and above all geriatric depression, is a challenge for “real-world” clinicians, due to the low rates of remission despite the increasing number of antidepressant strategies currently available. Indeed, current antidepressant strategies often fail to achieve acceptable rates of remission. The challenge of diagnosis and treatment of geriatric depression in real world calls for the need of a deeper exploration of its management in clinical practice. This is the purpose of the present cross-sectional survey, aimed at evaluating the clinical approach to late-life depression in a sample of expert physicians working in geriatric settings in Italy.MethodsHereafter, we provide responses from 175 geriatrics-working physicians, which were recruited to participate in the survey through their membership in the Italian Society of Geriatrics and Gerontology (SIGG). They were invited to respond to a a 20-items questionnaire which was developed based both on literature review and on the a priori knowledge of the subject by the developing team, composed by seven expert physicians in the fields of Psychiatry, Neurology and GeriatricsResults and discussionThe survey was aimed at delving into the possible unmet needs in the management of geriatric depression according to the sample of physicians surveyed, thus trying to provide useful insights on geriatric depression care.